TOX4 Inhibition in Chronic Hyperglycemia: Effects on Glycation Stress, Hepatic Protection, Epigenetic Mechanisms, Signaling Pathways, and Beta Cell Dynamics - Varunteja, Bonthu; Gupta, Nayan; Kumari, Anjali; Mukherjee, Tuhin; Mohanty, Satyajit; Nayak, Nikita; Chopra, Mahendra Pratap; Pattnaik, Ashok (Current Drug Metabolism, 2025)
TOX high mobility group box family member 4 (TOX4) has emerged as a critical regulator of Hepatic Glucose Production (HGP), particularly under insulin-resistant conditions seen in Type 2 Diabetes Mellitus (T2DM). Hyperglycemia-induced formation of Advanced Glycation End products (AGEs) exacerbates metabolic dysfunction. While the Akt-FoxO1 axis has been the conventional focus of insulin signaling, recent findings highlight the upregulation of TOX4 in T2DM, obesity, and preclinical models (e.g., db/db mice). The cAMP signaling pathway has been shown to modulate TOX4 expression. This review synthesizes findings from recent in vivo and in vitro studies investigating the role of TOX4 in hepatic metabolism. The study focuses on its regulatory mechanisms, interaction with insulin signalling pathways, and its modulation through pharmacological inhibition. TOX4 inhibition significantly reduces glucose output in hepatocytes and improves glucose tolerance in animal models. While TOX4 ablation fails to reverse metabolic impairments caused by insulin receptor knockout, it nonetheless attenuates hepatic glucose production under insulin-resistant states. Additionally, TOX4 suppression shows hepatoprotective effects and may offer potential neuroprotection in the context of diabetic complications. TOX4 represents a promising therapeutic target for managing T2DM and its comorbidities. Further investigation into selective TOX4 inhibitors and their long-term safety profiles could facilitate the development of adjunct therapies for metabolic disorders involving hepatic and neuronal dysfunction.
Keywords: diabetes mellitus